Implementing a Hybrid Ethnoscience Project-Based Learning (E-PjBL) Model Integrated with Virtual Assistive Technology to Enhance Critical Thinking Performance of Science Teacher Candidates - Wahyudi Wahyudi; Ahmad Harjono; Dwi Pangga (International Journal of Ethnoscience and Technology in Education, 2025)
Training critical thinking skills in science teacher candidates (STC) faces challenges, particularly due to the ineffectiveness of traditional teaching models, resulting in suboptimal critical thinking performance. This study aims to implement a Hybrid Ethnoscience Project-Based Learning (E-PjBL) model integrated with virtual assistive technology as a solution to enhance critical thinking performance in STC. A mixed-method approach combining quantitative and qualitative methods was utilized. An experimental design involving 51 STC at the University of Mataram was conducted, dividing participants into experimental and control groups. The experimental group engaged in learning activities using the hybrid E-PjBL model, while the control group followed traditional teaching methods. Quantitative data were collected through critical thinking skill tests administered pre- and post-intervention, while qualitative data were obtained from observations of learning implementation. Results demonstrated that the hybrid E-PjBL model significantly enhanced critical thinking skills compared to traditional methods. The experimental group’s posttest scores averaged 4.123, significantly higher than the control group’s 2.667. Statistical analysis using ANOVA revealed substantial differences in critical thinking scores between the groups, with an F-value of 99.613 (p < 0.001) for between-subject effects. Furthermore, a significant interaction was observed between test repetition (pretest-posttest) and group (control vs. experimental), with an F-value of 104.205 (p < 0.001). Qualitative findings indicated the model’s practicality, as evidenced by high student participation and engagement. These findings highlight that integrating ethnoscience, project-based learning, and virtual assistive technology offers an innovative and effective pedagogical approach to enhancing the quality of science teacher education. Further research is needed to explore the model's adaptability across diverse educational contexts.